2011
DOI: 10.1152/jn.00922.2010
|View full text |Cite
|
Sign up to set email alerts
|

A tingling sanshool derivative excites primary sensory neurons and elicits nocifensive behavior in rats

Abstract: Szechuan peppers contain hydroxy-α-sanshool that imparts desirable tingling, cooling, and numbing sensations. Hydroxy-α-sanshool activates a subset of sensory dorsal root ganglion (DRG) neurons by inhibiting two-pore potassium channels. We presently investigated if a tingle-evoking sanshool analog, isobutylalkenyl amide (IBA), excites rat DRG neurons and, if so, if these neurons are also activated by agonists of TRPM8, TRPA1, and/or TRPV1. Thirty-four percent of DRG neurons tested responded to IBA, with 29% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“…Singlefiber recordings have shown that, among identified cutaneous afferents, D-hair receptors are very strongly activated by hydroxy-␣-sanshool (42). However, this substance activates C-fiber nociceptors directly as well as RAMs; therefore, the behavioral effects of this substance will be the result of the ensemble activation of both mechanoreceptors and C fibers (32). Selective ways of activating Dhair receptors could be useful tools in the future to probe their precise functional role in sensation from the hairy skin.…”
Section: Figure 2 Mechanotransduction In Low-threshold Mechanorecepmentioning
confidence: 99%
“…Singlefiber recordings have shown that, among identified cutaneous afferents, D-hair receptors are very strongly activated by hydroxy-␣-sanshool (42). However, this substance activates C-fiber nociceptors directly as well as RAMs; therefore, the behavioral effects of this substance will be the result of the ensemble activation of both mechanoreceptors and C fibers (32). Selective ways of activating Dhair receptors could be useful tools in the future to probe their precise functional role in sensation from the hairy skin.…”
Section: Figure 2 Mechanotransduction In Low-threshold Mechanorecepmentioning
confidence: 99%
“…It is known from the unique somatosensory sensations of tingling and numbing it induces [5,6]. Previous neurophysiological studies using animal models (mice and rats) have demonstrated that the bioactive component of Szechuan pepper, hydroxyl-a-sanshool (hereafter sanshool), induces bursts of neuronal firing in specific cutaneous afferents through chemical events within the receptor membrane [7][8][9][10]. However, these studies focused on molecular receptor mechanisms and did not directly assess how chemical receptor events could relate to the tingling somatosensory experience.…”
Section: Introductionmentioning
confidence: 99%
“…Capsaicin, piperine, and zingerone all elicited irritant sensations of burning quality when applied to the lingual surface in humans (Green, 1993; Dessirier et al, 1999). Intraplantar administration of capsaicin evoked hindpaw licking and biting in rats and mice (Klein et al, 2011; Sakurada et al, 1992). Capsaicin, olvanil and piperine all evoked ocular wiping after corneal exposure in mice (Ursu et al, 2010; Karai et al, 2004).…”
Section: Resultsmentioning
confidence: 99%